Tomographical Findings in Adult Patients Undergoing Endoscopic Sinus Surgery Revision - Socher,Jan Alessandro (2018)
Abstract Introduction Many patients undergoing functional endoscopic sinus surgery still have an uncontrolled clinical disease in the late post-operative period. Up to 11.4% of the patients will require a revision surgery. Findings such as the residual uncinated process and the lateralization of the middle turbinate were considered by some studies as being responsible for failure in the primary surgery. Objectives To describe the tomographical findings in adult patients undergoing revision endoscopic sinus surgery, the profile of those patients, and verify the mucosal thickening level of the paranasal sinus. Methods Data were collected from medical records and computed tomography reports of 28 patients undergoing revision sinus surgery on a private service in the city of Blumenau between 2007 and 2014. The score of Lund-Mackay was used to verify the mucosal thickening level. Results Among the 28 patients, 23 were reoperated once, 3 were reoperated twice, and 2 were reoperated 3 times. The most relevant findings were mucosal thickening of the maxillary sinus (89.28%), deviated septum (75%), thickening of the ethmoid (50%) and sphenoidal sinuses (39.28%), and pneumatization of the middle turbinate (39.28%). The average obtained in the Lund-Mackay score was 5.71, withmost patients classified in the lower range of punctuation. Conclusion The analysis of the computed tomography scans showed persistent structures that may be responsible for the failure of the primary surgery. Computed tomography is a useful tool to plan the surgery and quantify the post-operative success.